Strategi Preservasi Digital di Perpustakaan STMIK AMIKOM Yogyakarta - T. Mulkan Safri (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
AMIKOM STMIK Library Yogyakarata is a library that hasimplemented a digitization system. All forms of library access are presentedin digital form, ranging from book collections, journals, to the use ofseveral other digital services. So that collections from digital libraries canbe used for a long time, a library needs to do digital preservation. Thisstudy aims to see how the strategy of the STIKIK AMIKOM library inYogyakarta to preserve digital collections. This research method usesdescriptive qualitative and data collection using interviews. The researchresults in this study are the AMIKOM STMIK library doing severalactivities such as; preservation and refreshing of digital devices and alsobacking up digital collections.